2017
DOI: 10.1002/jso.24631
|View full text |Cite
|
Sign up to set email alerts
|

Influence of neoadjuvant chemotherapy on resection of primary colorectal liver metastases: A propensity score analysis

Abstract: NC was not associated with increased OS in patients suffering from CRLM. Additionally, potentially harmful chemotherapy prior to surgery increases the risk of postoperative complications in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Several studies showed that there was no significant difference regarding survival between patients receiving simultaneous resections and staged resections [10,25]. This was also identified in a recent study [26]. In this study, the OS and RFS of patients undergoing simultaneous resection and staged resection did not differ significantly, and the OS was superior to that reported in those receiving palliative chemotherapy.…”
Section: Discussionsupporting
confidence: 75%
“…Several studies showed that there was no significant difference regarding survival between patients receiving simultaneous resections and staged resections [10,25]. This was also identified in a recent study [26]. In this study, the OS and RFS of patients undergoing simultaneous resection and staged resection did not differ significantly, and the OS was superior to that reported in those receiving palliative chemotherapy.…”
Section: Discussionsupporting
confidence: 75%
“…Strowitzki et al . showed that even in a total of 468 patients with colorectal liver metastases the administration of neoadjuvant chemotherapy is of questionable value 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Complications were separated into intra- and postoperative complications (such as severe bleeding or bile leakage) and non-surgical complications. 3 …”
Section: Methodsmentioning
confidence: 99%
“… 1 , 2 However, chemotherapy-induced liver damage and associated effects on oncologic outcomes need to be considered. 3 6 Chemotherapy-associated liver injury, such as hepatic steatosis, steatohepatitis and sinusoidal obstruction syndrome, occurs in up to 50% of patients receiving neoadjuvant chemotherapy (NC). 7 Negative effects of NC on hepatic functional reserve seem to be regimen-specific.…”
Section: Introductionmentioning
confidence: 99%